Survival of black holes through a cosmological bounce - Pérez, Daniela (2022)
We analyze whether a black hole can exist and survive in a universe that goes through a cosmological bounce. To this end, we investigate a central inhomogeneity embedded in a bouncing cosmological background modeled by the comoving generalized McVittie metric. Contrary to other dynamical metrics available in the literature, this solution allows for the interaction of the central object with the cosmological fluid. We show that the horizons associated with this metric change with cosmic time because they are coupled to the cosmic evolution as the mass of the central object is always proportional to the scale factor: it decreases during contraction and increases during expansion phases. After a full analysis of the causal structure of this spacetime, we determine that a dynamical black hole persists during the contraction, bounce, and expansion of the universe. This result implies that there is a class of bouncing models that admits black holes at all cosmological epochs. If these models are a correct approximation to the real universe, then black holes surviving a cosmic collapse could play some role in the subsequent expanding phase.